Effects of listening to Quran recitation and nature sounds on preoperative anxiety among patients undergoing surgery - Muhamad Ibrahim, Najhan; Mohd Zain, Uzair Idzwan Zain; Abdul Hadi, Azwanis; Ismail, Mohd Nizamuddin; Abd. Aziz, Karimah Hanim (National Institute of Psychology, Quaid-i-Azam University, Islamabad, Pakistan, 2022)
This study aimed to compare the effectiveness between listening to Quran and nature sounds on preoperative anxiety and physiological parameters. Using systematic random sampling, a randomized controlled trial study was conducted among 81 patients, which comprised of male and female patients allocated into three equal groups, that is, Quran recitation group, nature sounds group, and a control group. Preoperative state anxiety was measured using the State-Trait Anxiety Inventory (Embong, 2018), and physiological parameters were recorded before and after the intervention. After the intervention, the analysis within subjects showed significant improvement in heart rate, respiratory rate, and state anxiety. However, post-hoc test showed that reduction in the mean state anxiety scores in all groups was the only significant factor. Paired analysis showed that only mean state anxiety level of nature sounds group has a significant reduction in comparison to control group; whereas there was nonsignificant difference in state anxiety of other paired groups when compared between both intervened groups and between Quran group and control group. The result concluded that listening to either the Quran or nature sounds were effective in reducing preoperative anxiety, however head to-head comparison found no significant difference.